PENGARUH TIGA MEDIA TANAM SERBUK KAYU DAN PEMBERIAN DAN PEMBERIAN PUPUK PADA PRODUKSI JAMUR TIRAM PUTIH (Pleurotus ostreatus (var.) Florida) - Mahdi Fauzi; T. Chairun Nisa T. Chairun Nisa; Syukri Syukri (Jurnal Agroekoteknologi, 2013)
The aim of the study was to know the influence of three kinds of wood sawdust as planting media and P. fertilizer on the growth and yield of white champignon  (Pleurotus ostreatus). The study was cuonducted in a mold hut at Tanjung Mulia Hilir, Medan, at 25 meters above sea level, from April to July 2012. A Factorial Complete Randomized Design (CRD) was used with 2 factors, namely wood (rubber, mindi and durian), each was mixed with bran (“dedak”), calcium and gypsum, and phosphate fertilizer SP 36 at four level, namely (0 kg; 0,5 kg; 1 kg; and 1,5 kg/ 100 kg planting medium). Parameters observed were harvest age, stalk length, diameter of umbrella, umbrella thickness, number of umbrella per cluster, fresh weight per champignon, fresh weight champignon per baglog and biological efficiency ratio (BER). Result showed that sawdust from different wood significantly affected stalk length, diameter of umbrella, umbrella thickness, number of umbrella per cluster, fresh weight per champignon, fresh weight champignon per baglog and biological efficiency ratio (BER). Phosphate fertilizer significantly decreased all parameters. There were significant interaction effect on harvest age, umbrella diameter and thickness, number of umbrella per cluster and fresh wight per champignon.   Keywords: white champignon, wood sawdust as planting media, phosphate fertilizer